Effectiveness and cost-effectiveness of four different strategies for SARS-CoV-2 surveillance in the general population (CoV-Surv Study): study protocol for a two-factorial randomized controlled multi-arm trial with cluster sampling - Deckert, Andreas; Anders, Simon; De Allegri, Manuela; Nguyen, Hoa Thi; Souares-Coutant, Aurélia; McMahon-Rössle, Shannon A.; Meurer, Matthias; Burk, Robin; Sand, Matthias; Köppel, Lisa; Maier-Hein, Lena; Roß, Tobias; et al. (Trials, 2021)
To achieve higher effectiveness in population-based SARS-CoV-2 surveillance and to reliably predict the course of an outbreak, screening, and monitoring of infected individuals without major symptoms (about 40% of the population) will be necessary. While current testing capacities are also used to identify such asymptomatic cases, this rather passive approach is not suitable in generating reliable population-based estimates of the prevalence of asymptomatic carriers to allow any dependable predictions on the course of the pandemic.
Gesehen am 01.02.2022